2012
DOI: 10.1002/j.0022-0337.2012.76.12.tb05419.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Portfolio Assessment of Student Competence in Two Dental School Populations

Abstract: The purpose of this article is to describe the process and procedures involved in the implementation of portfolio assessment at two dental schools. Portfolios can be deined as a purposeful collection of student work that involves relection in which students identify gaps in their knowledge and abilities and develop strategies for correcting those gaps. Framed within the current context of dental education and the calls for change in the ways dental students are taught and assessed, these two dental schools emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
(26 reference statements)
0
24
0
Order By: Relevance
“…Like many U.S. dental schools over the last 25 years, the University of California, San Francisco (UCSF) School of Dentistry has employed various clinical curricula to ensure students obtain adequate clinical experience and attain required competencies for graduation. Dental schools have introduced such innovative curriculum and assessment formats as comprehensive care, 1 6 case completion, 7 , 8 competency examinations, 9 12 portfolios, 13 , 14 and community‐based, off‐campus externships 15 17 . UCSF has had three major clinical curricular changes since 1992, moving from a discipline‐based curriculum to a comprehensive care curriculum to a procedural requirement curriculum plus externships.…”
mentioning
confidence: 99%
“…Like many U.S. dental schools over the last 25 years, the University of California, San Francisco (UCSF) School of Dentistry has employed various clinical curricula to ensure students obtain adequate clinical experience and attain required competencies for graduation. Dental schools have introduced such innovative curriculum and assessment formats as comprehensive care, 1 6 case completion, 7 , 8 competency examinations, 9 12 portfolios, 13 , 14 and community‐based, off‐campus externships 15 17 . UCSF has had three major clinical curricular changes since 1992, moving from a discipline‐based curriculum to a comprehensive care curriculum to a procedural requirement curriculum plus externships.…”
mentioning
confidence: 99%
“…8 Another study researched the implementation of portfolio assessment for students' competence in dental schools and it indicated portfolios had useful results. 11 Another study was performed about the use of portfolios as a tool for assessment and professional development in graduate nursing education. 24 In this study the researcher found the positive effect of portfolio on post graduated.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, professors paid attention to the implementation of portfolio assessment to evaluate competence in dental students. 11 Some studies talked about the electronic portfolio as a way to encourage assessment. 12 Studies have been done on portfolios in nurses' education, [13][14][15] dental students, 16 medical students 17,18 and others.…”
Section: Introductionmentioning
confidence: 99%
“…Portfolios are a suitable form of assessment strategy that takes learning experience to the next level through student reflection. 13 …”
Section: Discussionmentioning
confidence: 99%